The Analysis of FoMO Behavior Based on Levels of Self-Esteem and Self-Concept: A Study among University Students - Nur Hafiza; Zadrian Ardi; Yeni Karneli; Rezki Hariko (Journal of Educational, Health and Community Psychology, 2024)
The purpose of this study is to examine FoMO (Fear of Missing Out) behavior based on levels of self-esteem and self-concept among university students. This research is correlational, employing multiple regression analysis. The sample consists of 313 first-year students from the Faculty of Education, Universitas Negeri Padang. The findings indicate that self-esteem among students is in the low category, with a total percentage of 47.4%. Similarly, self-concept is also in the low category, with a total percentage of 45.2%. On the other hand, FoMO among students is in the high category, with a total percentage of 69%. There is a negative and significant relationship between self-esteem and FoMO, as well as between self-concept and FoMO. Additionally, there is a simultaneous relationship between self-esteem, self-concept, and FoMO. The implications of the study suggest that the university needs to design guidance and counseling programs focused on enhancing students' self-esteem and self-concept to prevent the emergence of FoMO